PTSD, a Disorder with an Immunological Component - Wang, Zhewu; Young, M. Rita I. (Frontiers in Immunology, 2016)
Post-traumatic stress disorder (PTSD) has been associated with an inflammatory state. However, few studies have addressed the mechanisms underlying this immune imbalance that favors inflammation or how this imbalance contributes to PTSD. Whether the immune imbalance influences responsiveness or unresponsiveness of patients to PTSD treatments is currently not known. This review brings forward an immune emphasis to a mental health disorder that is unprecedented in its prevalence among combat Veterans of the ongoing conflicts in Iraq and Afghanistan, and which also afflicts civilians that have undergone extreme traumatic experiences such as following natural disasters, serious accidents or assaults. Included is an overview of the correlative associations in human subjects between PTSD and inflammation, and studies in animal models of PTSD demonstrating causal contributions of inflammation and immune dysregulation to PTSD-like behavior following stress exposure.